FIND THE BEAUTY IN INDONESIA WITH ONGIS TRAVEL - Diva Artha Puspita Sari; Joshua Anenlie; Marvanico Tjokrosoeharto; Husjina H. Suljic (International Journal of Applied Business and International Management, 2018)
Ongis travel is a tour operator which is located in Malang City, the hospitality that Ongis Travel offered as a guide to accompany your journey down the sights of interest in Malang City, East Java and beyond. Ongis Travel hope that visiting as a rarely activities will be more than just fun; therefore it is our pleasure to professionally make your sightseeing experience into recording a memorable footsteps. Malang City has a variety of charm in their tourism that is interesting to be explored. In this city Ongis Travel has been born and has been groing up by guiding domestic or foreign tourist. In the spirit of Ongis Travel services, we capture every moment of exquisite happiness. Therefore, the decision of choosing Ongis travel is a privilege worth. Ongis Travel marketing are up to date and they are using all kinds of social media like Instagram, website and Facebook. Ongis Travel update their tour in videos and post it on YouTube which the edit of the video, camera quality is too good to be compared with other tour and travel in Malang City. However, Ongis Travel post all of their marketing in Indonesian language so the foreign customers cannot actually understand it. Recomended Service Idea for Ongis Travel is to make a promotion using digital marketing that will be written or spoken in English language and Team 16 will make a business proposal regarding partnership with other tour and travel agency or agent in Europe and United State. In the business proposal there will be written both law regarding the agreement that both parties wanted. This proposal will be signed and approved in legal international business law. The distribution channel that has ben chosen by Team 16 are Tour and Travel Agency in USA and Europe, and Tour and Travel Agent. The partnership will be beneficial for both parties because Ongis Travel, Tour and Travel Agencies and Tour Agents will exchange customer, Indonesian traveler that wanted to travel to Europe or USA will be given to Tour and Travel Agencies and Tour Agents and Foreigners that apply in Tour and Travel Agencies and Tour Agents that wanted to travel to Indonesia will be given to Ongis Travel.